RESEARCH: "Religious Framing by Individuals With PTSD When Writing About Traumatic Experiences" - Exline, Julie J. (The international journal for the psychology of religion, 2005)
Writing about traumatic events can produce physical and psychological health benefits, especially when individuals use language to transform emotionally laden events into meaningful narratives. Because religion often facilitates the search for meaning, we predicted that the use of religious themes in writing would moderate mood-related outcomes. Fifteen individuals with posttraumatic stress disorder (PTSD) wrote in each of 3 sessions about their PTSD-triggering events. Religious themes were evident in essays written by 80 percent of participants. Relative to participants who did not frame their traumas in religious terms, those who used religious framing reported a greater shift toward negative mood after the first writing session than those without such framing. By the third session, however, religious framing was associated with more positive mood after writing, whereas nonreligious framing was still associated with more negative mood. The nature of religious references was important. Positive references and specific religious behaviors (e.g., prayer) were associated with more positive mood states, whereas negative religious references were not associated with mood. Implications for research and practice are discussed.